INTERFAITH MARRIAGE IN THE PERSPECTIVE OF TAFSIR - Hanafi, Sahrul (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Interfaith marriage is a complex social and legal phenomenon in Indonesia's pluralistic society. In Islam , marriage is not just a social contract, but part of worship that must be in accordance with the provisions of the Sharia. This paper analyzes the Qur'anic verses related to the law of interfaith marriage, especially QS. Al-Baqarah [2]:221, QS. Al-Mumtahanah [60]:10, and QS. Al-Maidah [5]:5, through classical and contemporary tafsir approaches. This study shows that Islam strictly prohibits marriage between Muslims and polytheists because it has the potential to damage faith and household stability, but provides limited exceptions for Muslim men to marry women of the Book under certain conditions. The different interpretations of scholars such as Imam Syafi'i, Ibn Kathir, Ibn Hazm, and Abu Hanifah reflect the dynamics of fiqh in understanding the social and theological context of each era. In the context of Indonesian positive law, through Law Number 1 of 1974 and the Compilation of Islamic Law (Presidential Instruction No. 1 of 1991), the state emphasizes that interfaith marriages are not valid according to Islamic law. Thus, the discussion of the interpretation of these legal verses provides a theological and normative basis that the sanctity of faith is the main foundation in the formation of an Islamic family in Indonesia.